Contribution of mineral filler to the fatigue damage behaviour of bituminous mastic - Chaudhary M.; Saboo N.; Gupta A.; Miljković M. (My University, 2025)
The objective of this research was to quantify the contribution of mineral filler to the linear shear strain amplitude sweep-based fatigue behaviour of mastic. Mastics with different volume fractions of mud (RM), marble dust (MD), and limestone dust (LS) fillers were tested in intermediate temperature domain, while the mechanical responses throughout the test sequence were compared to that of bitumen. The conspicuously high contribution of the RM filler indicated its comprehensive interaction with bitumen. The threshold of this contribution by approaching the ultimate particle interlocking was identified at the volume fraction of the RM filler of 20 %. On the contrary, the contributions of the common MD and LS fillers were moderate. The transition of the mechanical properties throughout the test sequence showed a characteristic dependency on the type of filler, its volume fraction, and test temperature. A more advanced characterisation of this transition in the zone of failure would have a considerable potential for the quantitative assessment of the type of failure, critical for the relevance of the results. © 2022 Elsevier Ltd